Bats as an Important Source of Antimicrobial-Resistant Bacteria: A Systematic Review - Julio D. Soto-López; Manuel Diego-del Olmo; Pedro Fernández-Soto; Antonio Muro (Antibiotics)
Background/Objectives: Bats are the second-largest known order of mammals, accounting for about twenty percent of the species described to date. This group has special importance in health and epidemiology because they are considered hosts of a wide range of antimicrobial-resistant human pathogens. Over the past few decades, the emergence of pathogenic bacteria resistant to antimicrobials has been a growing threat to public health, especially given its repercussions such as deaths associated with antimicrobial resistance and economic losses in the healthcare sector. Results: The diversity of antimicrobial-resistant bacteria, the different methodologies in numeric analysis, and the variety of antibiotics reported in this review make it difficult to establish the scope of the effect of bats on the antimicrobial resistance crisis. Methods: In this systematic review, we focus on the existence of antibiotic-resistant bacteria associated with bats and summarize the main findings of studies conducted on the topic to date. Conclusions: Surveillance is essential to control the emergence of resistant bacteria related to bats, which could eventually affect humans, as this is a problem of a ‘One Health’ nature, with effects on human, animal, and environmental health.